Strategies for decreasing contamination of homemade nasal saline irrigation solutions. Issue 2 (20th August 2015) - Hardy, Elliot T.; Stringer, Scott P.; O'Callaghan, Richard; Arana, Angela; Bierdeman, Michael A.; May, Warren L.
Abstract : Background: Saline nasal irrigations (SNI) are an important adjunct in the treatment of rhinosinusitis, and many patients prepare and store these solutions in their homes without an awareness of the potential for contamination. The objectives of this study were to determine if such contamination occurs and the effect of preparation methods on contamination. Methods: Stock solutions of various tonicities and pHs were prepared using boiled, bottled, and distilled water (n = 57). The solutions were stored at ambient temperature or refrigerated for 1 week. Each day, 50 mL of the solutions were decanted to simulate transferring the stock solution into an irrigation vector. Cultures of the stock solutions were taken on days 1, 3, and 7. Results: Overall contamination rate was 35.1%. The boiled water solutions were more likely to demonstrate bacterial growth ( p < 0.001), as were those that were hypotonic ( p = 0.046). pH had no significant effect ( p = 0.127). Growth occurred as early as 24 hours after solution preparation. Pathogenic species isolated were Staphylococcus aureus, Moraxella sp, Sphingomonas paucimobilis, Acinetobacter junii, Methylobacterium sp, and Brevundimonas diminuta . No bacterial growth occurred in refrigerated solutions ( p = 0.008). Conclusion: Pathogenic bacterial growth can occur in a short period of time in homemade SNI solutions with routine handling. Solutions should be refrigerated if possible. If solutions are to be stored at ambient temperature, they should be either isotonic or hypertonic and prepared from bottled or distilled water.